The Effectiveness of Wordwall in Enhancing Arabic Vocabulary Mastery Among Fourth-Grade Students at SDIT An Najiyah Pekanbaru - Ainiyyah Wil Dhani; Resy Mulyani (Journal of Practice Learning and Educational Development, 2026)
Mastering vocabulary is essential for developing proficiency in the Arabic language. However, elementary school students often struggle to memorise and comprehend Arabic vocabulary. One contributing factor is the limited use of engaging learning materials that encourage active participation. This study aimed to determine the effectiveness of the wordwall platform in improving Arabic vocabulary mastery among Year 4 students at SDIT An Najiyah in Pekanbaru. A pre-experimental method was employed using a one-group pretest-posttest design, involving 26 female students in Year 4. Data were collected through written tests administered before and after the intervention, and analysed using the Wilcoxon signed-rank test and the N-Gain Test. The results showed that the mean score increased from 85.58 in the pre-test to 96.15 in the post-test. The Wilcoxon test revealed a significance value of p < 0.001, indicating a statistically significant improvement in vocabulary mastery among the students after the intervention. Furthermore, the N-Gain score was 77.85%, falling into the high category. These findings suggest that the wordwall platform effectively enhances Arabic vocabulary mastery among fourth-grade students at SDIT An Najiyah Pekanbaru.